2013
DOI: 10.1002/aur.1297
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Stapedial Reflex Reveals Delayed Responses in Autism

Abstract: Autism is a developmental disorder characterized, in part, by sensory abnormalities. It is well established that most if not all patients with autism have problems with auditory processing, ranging from deafness to hyperacusis, and physiological testing of auditory function (i.e. auditory brain stem responses) implicates brain stem dysfunction in autism. Additionally, previous research from this lab has revealed significantly fewer auditory brain stem neurons in autistic subjects as young as 2 years of age. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 79 publications
(98 reference statements)
2
14
0
Order By: Relevance
“…As regard to ipsilateral and contralateral acoustic reflex thresholds at different frequencies, there was no statistical significant differences between right and left ears in each group as well as a none statistical significant differences between groups .This conclusion agree with that of Lukose et al (14) who also found that autistic subjects had lower ipsilateral acoustic reflex thresholds at only 500 and 1,000 Hz. However, this finding may be related to deficits in inhibitory neurotransmission.…”
Section: Discussionsupporting
confidence: 90%
“…As regard to ipsilateral and contralateral acoustic reflex thresholds at different frequencies, there was no statistical significant differences between right and left ears in each group as well as a none statistical significant differences between groups .This conclusion agree with that of Lukose et al (14) who also found that autistic subjects had lower ipsilateral acoustic reflex thresholds at only 500 and 1,000 Hz. However, this finding may be related to deficits in inhibitory neurotransmission.…”
Section: Discussionsupporting
confidence: 90%
“…Integrity of the auditory brainstem nuclei can be accessed through a number of noninvasive techniques, such as brainstem auditory evoked potentials (BAEPs), otoacoustic emissions, speech recognition tasks and listening in background noise. Incidentally, similar morphological alterations were observed in autistic children (Kulesza and Mangunay, 2008; Kulesza et al, 2011) and correlated with abnormal brainstem reflexes (Lukose et al, 2013). Urban children have delayed central conduction time of brainstem neural transmission, resulting in increased risks for auditory and vestibular impairments and altered speech recognition abilities (Calder贸n-Garcidue帽as et al, 2011b).…”
Section: Children鈥檚 Systemic and Brain Effects Of Air Pollutionmentioning
confidence: 58%
“…performed a detailed quantitative study of the ASR in a group of 29 control participants (ages 7-17 years) and 54 participants with ASD (ages 4-23 years) who were verbal and cooperative with the examiner. 68 We found that children with ASD had significantly lower thresholds and significantly longer latency responses. Longer latencies were most prominently observed for ipsilateral-driven responses to a 1-kHz stimulus.…”
Section: Auditory Dysfunction In Asdmentioning
confidence: 64%
“…The literature provides an abundance of data supporting both abnormal structure and function in the As we stated previously 68 91 There is also evidence that auditory integration training normalizes brainstem responses in children with ASD and even improves behaviors. 92 Additional research in these areas will result in better integration and outcomes for children with ASD.…”
Section: Recommendation and Conclusionmentioning
confidence: 80%